Kualitas Kepemilikan Pengetahuan Simbol Melayu Bidang Permainan di Kalangan Mahasiswa - Hermandra, Hermandra; Mustafa, M. Nur; Zulhafizh, Zulhafizh (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This research was motivated by technological advances that have influenced traditional games' popularity as symbols of culture, so it is necessary to preserve and maintain them through the quality of knowledge. How can the quality of possession of knowledge of Malay symbols in the field of play among FKIP Riau University students be formulated? The research objective was to analyze and describe the quality of possession of knowledge of Malay symbols in the field of play among FKIP students at the University of Riau. This research used a descriptive quantitative approach—observation of knowledge with a likert scale. The observation sample was 870 people from a population of 6300 people or 13.8% of 100%. The sample was taken randomly based on questionnaire filling and collection. The technique of collecting data employed a questionnaire related to the traditional games of the Riau Malay community. The process of collecting data distributed through a google form. The collected data were substituted and analyzed with descriptive statistics, Product Moment, and Anova. The analysis results showed that students' knowledge regarding traditional games of the Malay community as a cultural symbol was at a standard of mean 4.37 with a very high category. The games of gasing, bakiak, congkak, enggrang, layang-layang, tarik tambang, petak umpet, benteng, ligu, and statak can contribute information to knowledge ownership of the games of the Riau Malay community by 35.9%. In comparison, other games were at 64.1%. The possession of this knowledge has supported documenting various games and preserving the existence of these games. Besides, the content of values ​​in the game is a means of character education and supports learning and learning activities.